Língua portuguesa e língua inglesa: questões de imaginário em (du)elo - Hübner, Jancileidi (2019)
This dissertation analyzes the subject-student’s discourse in order to comprehend the forms of imaginary of the mother tongue and the foreign language that circulates in the schooling space of both languages. Five subject-students from a university in the north of Rio Grande do Sul who have the Portuguese language as their mother tongue and study the English language as a foreign language participated in this research. By writing narratives, the subject-students discursivized experiences and memories related to the process of teaching and learning of languages and the importance those languages have in their lives. From the analysis of the written narratives, it was possible to highlight the following forms of imaginary of language: language of correction, guided by the conception of language as an educated norm which is far from the fluid language and, as a consequence, the imaginary of the Portuguese language as a difficult language; language as a school content to be learned or as a school subject; language as a tool based on an instrumentalist conception of language; and the imaginary of the English language as a world language. We considered the fact that these images are products of the identifications of the subject-student within the process of teaching and learning of languages and also constitutive of their subjectivity. As a result, we consider the possible existence of links and duels between the mother tongue and the foreign language in the space with imprecise and unclear limits between the schooling of both languages which, consequently, cross the identitary constitution that emerge from this space.